BEYOND HUMAN COMMUNICATION: THE ARTIFICIAL INTELLIGENCE PHENOMENON IN THE PERSPECTIVE OF COMMUNICATION THEORY - Prahastiwi Utari; Pramana Pramana; Amelia Ramadhani (Interaksi: Jurnal Ilmu Komunikasi, 2024)
The study of the Artificial Intelligence (AI) phenomenon has developed rapidly in recent years by placing various multi-disciplinary perspectives including Communication. The question then arises, how to study the AI phenomenon with a Communication approach? What kind of communication theories can be used to explain the AI phenomenon? Can the existing perspective of communication theory, which emphasizes the notion of communication as an interaction in which two communicators, using some medium of communication, move towards a better understanding of each other through the exchange of messages, still be used? Is the communication theory domain in terms of elements, levels and contexts of communication still relevant to studying the AI phenomenon? Is there a possibility of developing a new group of theories in studying AI phenomena?. This paper will provide an inspiring perspective on the development of a group of communication theories called "Beyond Human Communication" (Littlejohn, 2021). This broader view of communication includes interactions between humans and other animate and inanimate entities. It provides opportunities to examine different ways and different reasons for communicating. AI phenomena in the "Beyond Human Communication" theoretical domain can be explained through what is referred to as "human-machine communication". Understanding the theoretical domain of "Beyond Human Communication" places the study of the AI phenomenon into a special study in Communication science.